Faktor-Faktor Yang Mempengaruhi Opini Audit Going Concern Pada Persuahaan Manufaktur - Stella Ferdy, Jamaludin Iskak (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research examine about the effect of profitability, financial distress, and leverage toward audit going concern opinion on manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2019 period. This research used purposive sampling technique, there are 30 companies after filtered. Hence there are 90 samples used in this research for three years. The data was analyzed with logistic regression analysis that run by Statistical Product and Service Solution 25 for windows and Microsoft Excel 2016. Based on the analysis results, revealed that profitability and leverage have no significant effect, while financial distress has significant effect toward audit going concern opinion. Implication from the study is that auditor need to consider other things than just profitability, financial distress, and leverage. There are many other factors to be considered for auditor to not issue going concern.